High crystallinity graphite protective layer and preparation method thereof
By preparing a high-crystalline graphite protective layer on the surface of porous graphite and using suspensions of carbides and metal sintering agents for high-temperature sintering, the problems of poor conductivity, thermal conductivity and poor thermal expansion characteristics of the graphite protective layer in the prior art are solved, and efficient improvement of thermal conductivity, electrical conductivity and structural integrity are achieved.
Patent Information
- Application Number
- CN202411666553.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-04
AI Technical Summary
The graphite protective layer prepared on the porous graphite surface has problems such as electrical conductivity, poor thermal conductivity, and poor thermal expansion characteristics. The sintering density of the coating is low and lacks sufficient oxidation resistance and mechanical strength.
By placing the carbide and metal sintering agent into a uniform suspension in a certain proportion, applying it to the graphite surface and sintering at a high temperature, forming a high crystallinity graphite protective layer. The method includes ball milling and finening, sonication, room temperature and vacuum drying, stepwise heating and sintering, etc. to optimize the crystal quality and performance of the graphite protective layer.
The graphite protective layer has achieved high crystallinity, improved thermal conductivity, reduced oxidation mass loss, reduced resistivity, improved thermal expansion characteristics, and significantly improved overall performance and structural integrity of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-crystallinity graphite protective layers, and in particular to high-crystallinity graphite protective layers and a preparation method thereof. Background Art
[0002] Graphite is a common thermal field material with excellent high temperature resistance, thermal shock resistance and heat resistance. According to the different crystal forms, it includes three categories: dense crystalline graphite, flake graphite, and cryptocrystalline graphite. Artificial graphite can be regarded as a multiphase material, which is porous graphite. Graphene is a single-layer carbon atom plane material in which carbon atoms are arranged hexagonally into a two-dimensional honeycomb crystal structure, with excellent electrical, thermal, mechanical and optical properties. Compared with dense crystalline graphite, artificial porous graphite has poor thermal and electrical conductivity. By impregnating metal on the surface of porous graphite, it can achieve densification, enhance mechanical strength, and improve material wear resistance, heat resistance and impact resistance. However, the thermal expansion coefficient of the impregnated metal is large and the heat resistance is poor. Therefore, it is crucial to develop a graphite protective layer with a graphene-like structure prepared on the surface of porous graphite to improve its oxidation resistance, mechanical strength and the electrical and thermal conductivity of the overall graphite material.
[0003] The prior art discloses a method for preparing a tantalum carbide coating with controllable thickness on the surface of graphite, wherein a mixed salt is subjected to a molten salt reaction to react a tantalum source with graphite, followed by carburizing to infiltrate carbon into the surface and nanopores of the tantalum carbide formed by the previous molten salt reaction, and then subjected to a molten salt reaction treatment to increase the thickness of the tantalum carbide, and finally subjected to a high-temperature treatment to make the tantalum carbide grains grow and densify, thereby obtaining a uniform, dense, and high-purity tantalum carbide coating. The problem that the molten salt method cannot grow a thick single-phase coating is overcome, and the corrosion resistance and service life of the coating are improved, but the carbon and tantalum carbide of the graphite surface coating are alternately distributed, and the surface coating has certain defects. The prior art discloses an aqueous suspension containing metal carbide particles, comprising metal carbide particles, a sintering aid cobalt, and a C dispersant, which is dried under an inert gas to obtain a crack-free coating, but the sintered density of the formed coating is low. Summary of the invention
[0004] In order to develop a high-crystallinity graphite protective layer with a graphene-like structure prepared on the surface of porous graphite, the present invention aims to achieve a crystal morphology, flatness and larger grain size that is superior to natural graphite and other traditional graphite materials. Thereby, the oxidation resistance itself can be improved to a certain extent, the mechanical strength and the electrical and thermal conductivity of the overall graphite material can be improved, and the thermal expansion characteristics can be reduced. The first aspect of the present invention provides a high-crystallinity graphite protective layer. The present invention configures carbides and metal sintering agents into a uniform suspension in a certain proportion, applies them to the graphite surface, and obtains them after high-temperature sintering. Due to the layered structure characteristics of graphite, the protective layer not only has excellent physical properties, but also effectively improves the overall performance of graphite. By adjusting the process parameters such as sintering raw materials, powder uniformity and particle size, and heating rate, the crystal quality and performance of the graphite protective layer can be further optimized.
[0005] As a preferred embodiment, the thermal conductivity of the high crystallinity graphite protective layer is ≥55 W / m·K, the oxidation mass loss is ≤33%, and the resistivity is ≤14×10 -4 Ω·cm.
[0006] As a preferred embodiment, the raw materials for preparing the high-crystallinity graphite protective layer include carbide and a metal sintering agent, the weight ratio of the carbide to the metal sintering agent is (2-7): (1-5), and the raw materials for preparing the high-crystallinity graphite protective layer also include a solvent and a dispersant.
[0007] As a preferred embodiment, the weight ratio of the carbide to the metal sintering agent is (4-6): (1-2).
[0008] As a preferred embodiment, the weight ratio of the carbide to the metal sintering agent is (4:1), (5:1), (6:1), (4:2), (5:2), (6:2).
[0009] As a preferred embodiment, the weight ratio of the carbide to the metal sintering agent is 5:2.
[0010] As a preferred embodiment, the carbide includes at least one of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and tantalum zirconium carbide.
[0011] As a preferred embodiment, the carbide includes at least one of tantalum carbide, tungsten carbide and molybdenum carbide.
[0012] As a preferred embodiment, the carbide is tantalum carbide.
[0013] As a preferred embodiment, the metal sintering agent includes at least one of iron, cobalt, nickel, niobium and zirconium.
[0014] As a preferred embodiment, the metal sintering agent includes at least one of iron, cobalt and nickel.
[0015] As a preferred embodiment, the metal sintering agent is cobalt.
[0016] As a preferred embodiment, the particle size of the carbide is 500nm-1500nm, and the particle size of the metal sintering agent is 500nm-1500nm.
[0017] As a preferred embodiment, the particle size of the carbide is 700nm-1000nm, and the particle size of the metal sintering agent is 700nm-1000nm.
[0018] As a preferred embodiment, the particle size of the carbide is 800 nm, and the particle size of the metal sintering agent is 800 nm.
[0019] The applicant found that mixing carbide with a metal sintering agent to form a suspension, applying it to the graphite surface and then sintering can produce the effect of lowering the reaction melting point and catalyzing the migration, precipitation and crystallization of the C component. The possible reason is speculated to be: tantalum carbide is mixed with a metal sintering agent and then applied to the graphite surface. During the high-temperature sintering process, a carbide polycrystalline layer is first formed on the graphite surface, which serves as a catalytic substrate to promote the subsequent crystallization growth of graphene or polycrystalline graphite. The carbide layer can provide an effective carbon source to accelerate the graphite crystallization reaction. When the sintering temperature rises to the melting point of the sintering agent, the free carbon from the graphite and carbide migrates to the top layer to form a self-limiting thick layer of graphene or polycrystalline graphite. The high-crystallinity thick layer of crystalline graphite formed by free carbon has excellent thermal conductivity and electrical conductivity, and is resistant to high-temperature oxidation and avoids the characteristics of high-temperature infiltration of graphite dust.
[0020] A second aspect of the present invention provides a method for preparing a high-crystallinity graphite protective layer, comprising the following steps:
[0021] The carbide and the metal sintering agent are mixed and refined to obtain a mixed powder;
[0022] Adding a solvent and a dispersant to the mixed powder to obtain a mixed solution I;
[0023] Stirring the mixed solution I until there are no particles, and then ultrasonicating the mixed solution II;
[0024] Adhere the mixed solution II to the surface of the workpiece to be treated and dry;
[0025] After drying and sintering, a high-crystallinity graphite protective layer is obtained.
[0026] As a preferred embodiment, the preparation process of the mixed powder includes: ball milling, the rotation speed of the ball milling is 100r / min-700r / min, and the ball milling time is 10h-30h.
[0027] As a preferred embodiment, the preparation process of the mixed powder includes: ball milling, the rotation speed of the ball milling is 300r / min-600r / min, and the ball milling time is 15h-25h.
[0028] As a preferred embodiment, the preparation process of the mixed powder includes: ball milling, the rotation speed during ball milling is 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min; the ball milling time is 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h.
[0029] As a preferred embodiment, the preparation process of the mixed powder includes: ball milling, the rotation speed of the ball milling is 500r / min, and the ball milling time is 20h.
[0030] As a preferred embodiment, the preparation process of the mixed solution II includes: using an ultrasonic machine for ultrasonication, the horn type of the ultrasonic machine is 20-30, the frequency of the ultrasonic machine is 15KHz-25KHz, the power of the ultrasonic machine is 1000W-2000W, and the ultrasonic time of the ultrasonic machine is 5min-15min.
[0031] As a preferred embodiment, the preparation process of the mixed solution II includes: using an ultrasonic machine for ultrasonication, the horn type of the ultrasonic machine is 20-25, the frequency of the ultrasonic machine is 20KHz-25KHz, the power of the ultrasonic machine is 1500W-2000W, and the ultrasonic time of the ultrasonic machine is 9min-13min.
[0032] As a preferred embodiment, the power of the ultrasound machine is 1000W, 1100W, 1200W, 1300W, 1400W, 1500W, 1600W, 1700W, 1800W, 1900W, or 2000W.
[0033] As a preferred embodiment, the output power of the ultrasound machine is 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90%.
[0034] As a preferred embodiment, the ultrasonic time of the ultrasonic machine is 5 minutes, 10 minutes, 15 minutes, or 20 minutes.
[0035] As a preferred embodiment, the preparation process of the mixed solution II includes: using an ultrasonic machine for ultrasonication, the horn type of the ultrasonic machine is 25, the frequency of the ultrasonic machine is 20.5KHz, the power of the ultrasonic machine is 1800W, and the ultrasonic time of the ultrasonic machine is 10min.
[0036] As a preferred embodiment, the preparation process of the mixed solution II includes: replenishing the solvent during ultrasound, the interval time of the solvent replenishment is 1min-3min, multiple ultrasounds are required, the interval time of the ultrasounds is 5s-15s, and the number of ultrasounds is 3-8 times.
[0037] As a preferred embodiment, the preparation process of the mixed solution II includes: replenishing the solvent during ultrasound, the interval time of the solvent replenishment is 1min-2min, multiple ultrasounds are required, the interval time of the ultrasounds is 8s-12s, and the number of ultrasounds is 4-6 times.
[0038] As a preferred embodiment, the preparation process of the mixed solution II includes: replenishing the solvent during ultrasound, the interval time of the solvent replenishment is 1 minute, multiple ultrasounds are required, the interval time of the ultrasounds is 10 seconds, and the number of ultrasounds is 5 times.
[0039] The present invention adopts multiple ultrasonic treatments and continuously replenishes solvent during the ultrasonic process, which can prevent excessive evaporation of the solvent in the suspension and avoid agglomeration of the suspension slurry. Multiple ultrasonic treatments are used to obtain a uniform and stable mixed solution. The particle size of the formed mixed solution II is uniform, and the obtained coating is flat and has fewer defects.
[0040] As a preferred embodiment, the particle size of the mixed powder in the mixed solution II is 2nm-20nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 10μm-30μm.
[0041] As a preferred embodiment, the particle size of the mixed powder in the mixed solution II is 2nm-10nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 15μm-25μm.
[0042] As a preferred embodiment, the particle size of the mixed powder in the mixed solution II is 2 nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 20 μm.
[0043] As a preferred embodiment, the attachment method of the mixed solution II includes but is not limited to brushing, spraying, dipping, etc.
[0044] As a preferred embodiment, the mixed solution II is attached by brushing.
[0045] As a preferred embodiment, the drying includes room temperature drying and vacuum drying oven drying, the room temperature drying time is 0.5h-1.5h, the vacuum drying oven drying temperature is 70°C-160°C, and the vacuum drying oven drying time is 1h-5h.
[0046] As a preferred implementation, the room temperature drying time is 45 min-80 min; preferably, the room temperature drying time is 1 h.
[0047] As a preferred embodiment, the vacuum drying oven drying comprises: stepwise drying at 70°C-90°C, 110°C-130°C, 140°C-160°C for 3h-5h, 2h-4h, 1h-2h respectively.
[0048] As a preferred embodiment, the vacuum drying oven drying comprises: stepwise drying at 80°C, 120°C, and 150°C for 4h, 3h, and 1h respectively.
[0049] The present invention first performs preliminary drying at room temperature, and then places the coating in a vacuum drying oven and gradually heats up for drying. The formed coating is not easy to crack, and the large-grained high-crystallinity graphite layer is tightly stacked without cracks and holes. The reason may be that the gradual drying method can avoid the situation where the coating is dry on the outside and wet on the inside, and prevent the coating from rapidly heating up during the sintering process to cause cracking.
[0050] As a preferred embodiment, the sintering includes: sintering in an inert gas slightly positive pressure environment, heating to 800°C-2100°C at a heating rate of 3°C / min-5°C / min, keeping warm for 10min-30min respectively, then heating to 2500°C-2700°C at a heating rate of 1°C / min-3°C / min, keeping warm for 1h-3h, and cooling naturally.
[0051] As a preferred embodiment, the sintering includes: sintering in an inert gas slightly positive pressure environment, heating to 800℃-900℃, 1400℃-1600℃, 1700℃-1900℃, 2000℃-2100℃ at a heating rate of 4℃ / min-5℃ / min, keeping warm for 15min-25min respectively, then heating to 2550℃-2650℃ at a heating rate of 1℃ / min-2℃ / min, keeping warm for 1h-2h, and cooling naturally.
[0052] As a preferred embodiment, the sintering includes: sintering in an inert gas slightly positive pressure environment, heating to 800°C, 1500°C, 1800°C, and 2100°C at a heating rate of 5°C / min, keeping warm for 20 minutes respectively, then heating to 2600°C at a heating rate of 1°C / min, keeping warm for 1 hour, and cooling naturally.
[0053] As a preferred embodiment, the slight positive pressure is 103 kPa-104 kPa.
[0054] As a preferred embodiment, the inert gas includes but is not limited to argon, nitrogen, helium and the like.
[0055] As a preferred implementation, the inert gas is argon.
[0056] As a preferred embodiment, in the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is (1-5):1.
[0057] As a preferred embodiment, in the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is (2-4):1.
[0058] As a preferred embodiment, in the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is (2:1), (3:1), or (4:1).
[0059] As a preferred embodiment, in the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is 3:1.
[0060] As a preferred embodiment, the dispersant accounts for 1-5% of the total mass of the mixed solution I.
[0061] As a preferred embodiment, the dispersant accounts for 2-4% of the total mass of the mixed solution I.
[0062] As a preferred embodiment, the dispersant accounts for 2%, 2.5%, 3%, 3.5%, or 4% of the total mass of the mixed solution I.
[0063] As a preferred embodiment, the dispersant accounts for 3% of the total mass of the mixed solution I.
[0064] As a preferred embodiment, the amount of the supplementary solvent in the process of preparing the mixed solution II is 3-8% of the mass of the solvent in the process of preparing the mixed solution I.
[0065] As a preferred embodiment, the amount of the supplementary solvent in the process of preparing the mixed solution II is 4-6% of the mass of the solvent in the process of preparing the mixed solution I.
[0066] As a preferred embodiment, the amount of solvent added during the preparation of mixed solution II is 4%, 4.5%, 5%, 5.5%, or 6% of the mass of the solvent during the preparation of mixed solution I.
[0067] As a preferred embodiment, the amount of solvent added during the preparation of mixed solution II is 5% of the mass of the solvent used during the preparation of mixed solution I.
[0068] As a preferred embodiment, the solvent includes but is not limited to anhydrous ethanol, ethyl acetate, benzene, water and other solvents.
[0069] As a preferred embodiment, the solvent is anhydrous ethanol.
[0070] As a preferred embodiment, the dispersant includes but is not limited to polyvinyl butyral, silane, ethylene-vinyl acetate copolymer and other dispersants.
[0071] As a preferred embodiment, the dispersant is polyvinyl butyral.
[0072] As a preferred embodiment, the high crystallinity graphite protective layer is applied to the surface of the graphite part.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] (1) The high-crystallinity graphite protective layer of the present invention is a combination of 800nm tantalum carbide and 800nm cobalt, and the weight ratio of tantalum carbide to cobalt is (4-6): (1-2). The high-crystallinity graphite protective layer formed on the graphite surface is not easy to peel and flake off, and has high integrity.
[0075] (2) The method for preparing the high-crystallinity graphite protective layer of the present invention adopts an ultrasonic machine with a horn type of 25, an ultrasonic frequency of 20.5KHz, an ultrasonic power of 1800W, and an ultrasonic time of 10min for ultrasonication. The powder of the mixed solution II formed has a small particle size of 2nm-10nm, and the suspension is evenly dispersed. The formed large-grained, high-crystallinity graphite layer is tightly stacked, the grain size is uniform, and there are no obvious cracks and holes.
[0076] (3) The method for preparing the high-crystallinity graphite protective layer of the present invention adopts a drying method combining room temperature drying and vacuum drying, and then gradually increases the temperature for sintering. The surface of the formed protective layer is entirely graphite, and there is no low-melting-point impurity phase retained in the initial raw materials such as sintering agent. The obtained high-crystallinity graphite protective layer has a high degree of graphitization and few defects.
[0077] (4) The method for preparing the high-crystallinity graphite protective layer of the present invention continuously replenishes the solvent during the ultrasonic process and performs ultrasonic treatment multiple times, which can maintain the uniform dispersion of the suspension, avoid agglomeration of the suspension, and improve the convenience of the experiment.
[0078] (5) The method for preparing a high-crystallinity graphite protective layer of the present invention is used on the surface of a graphite part to form a large-grain high-crystallinity graphite layer, which improves the chemical corrosion resistance and high-temperature oxidation resistance of the graphite substrate and avoids the high-temperature permeation of graphite dust. The large-grain high-crystallinity graphite layer is tightly combined with the graphite substrate, which reduces the thermal expansion coefficient of the overall graphite material, increases the crystal density, reduces the oxidation mass loss rate, increases the thermal conductivity, specific heat, and thermal diffusion coefficient, and reduces the resistivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 This is an electron microscope image of the high crystallinity graphite protective layer prepared in Example 1;
[0080] Figure 2 This is the infrared spectrum of the high crystallinity graphite protective layer prepared in Example 1;
[0081] Figure 3 This is the XRD spectrum of the high crystallinity graphite protective layer prepared in Example 1;
[0082] Figure 4 This is an electron microscope image of the high crystallinity graphite protective layer prepared in Example 2;
[0083] Figure 5 This is the XRD spectrum of the high crystallinity graphite protective layer prepared in Example 2;
[0084] Figure 6 This is an electron microscope image of the high crystallinity graphite protective layer prepared in Example 3;
[0085] Figure 7 This is the XRD spectrum of the high crystallinity graphite protective layer prepared in Example 3;
[0086] Figure 8 This is an electron microscope image of the high crystallinity graphite protective layer prepared in Example 4;
[0087] Fig. 9 This is the XRD spectrum of the high crystallinity graphite protective layer prepared in Example 4;
[0088] Fig.10 This is the XRD pattern of the single crystal graphite protective layer prepared in Example 5;
[0089] Figure 2-10 Middle: a: workpiece to be processed (graphite); b: graphite protective layer; c: tantalum carbide; d: molybdenum carbide; e: tungsten carbide; f: single crystal graphite.
[0090] Fig.11 This is an electron microscope image of the single crystal graphite protective layer prepared in Example 5;
[0091] Fig.12 This is the eds element distribution diagram of the mixed powder after ball milling in step S1 in Example 1;
[0092] Fig.13 This is an electron micrograph of the mixed powder in Example 6 before ball milling;
[0093] Fig.14 This is an electron microscope image of the graphite protective layer prepared in Example 6 without ball milling;
[0094] Fig.15 The surface morphology of the crystalline graphite layer prepared under different ball milling parameters in Example 6;
[0095] Fig.16 The electron micrographs of the mixed powder prepared under different ultrasonic parameters (step S3) in Example 7;
[0096] Fig.17 The electron microscope images of the high crystallinity graphite protective layer prepared under different ultrasonic parameters in Example 7;
[0097] Fig.18 This is an electron microscope image of the high crystallinity graphite protective layer prepared in Example 9;
[0098] Fig.19 This is an electron microscope image of the graphite protective layer prepared in Example 10;
[0099] Fig. 20 This is an electron microscope image of the high-crystallinity graphite protective layer prepared in Example 11. DETAILED DESCRIPTION
[0100] In order to improve the protective effect of the graphite layer on the graphite substrate, improve oxidation resistance, mechanical strength, electrical and thermal conductivity, increase crystal density, reduce oxidation mass loss rate, increase thermal conductivity, specific heat, thermal diffusion coefficient, and reduce resistivity, the present invention provides a high-crystallinity graphite protective layer and preparation method, which are used on the surface of graphite parts. Carbides and metal sintering agents are configured into a uniform suspension in a certain proportion, applied on the graphite surface, and obtained after high-temperature sintering. The combination of carbides such as tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, tantalum zirconium carbide and sintering agents such as iron, cobalt, nickel, niobium, and zirconium can produce the characteristics of melting point reduction and catalysis, and a layer of carbide coating (tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, tantalum zirconium carbide) is first formed on the surface of graphite, and becomes the basis for the growth of thick graphene layers, that is, catalytic surface. Free carbon components (derived from graphite substrate and carbide powder) migrate to the top layer during high-temperature sintering, and continuously form self-limiting thick layers of graphene or polycrystalline graphite. The large-grained, high-crystallinity graphite layer can provide the graphite substrate with higher electrical and thermal conductivity, high-temperature oxidation resistance protection, and avoid high-temperature infiltration of graphite dust.
[0101] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the materials and equipment used are all commercially available. If in the following examples, specific processing conditions and processing methods are not clearly described, then conditions and methods known in the art can be used to process.
[0102] Example 1
[0103] A high-crystallinity graphite protective layer, the preparation raw materials include carbide and metal sintering agent, the weight ratio of the carbide to the metal sintering agent is 5:2, and the preparation raw materials also include solvent and dispersant.
[0104] The carbide is tantalum carbide; the metal sintering agent is cobalt; the solvent is anhydrous ethanol; the dispersant is polyvinyl butyral, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a weight average molecular weight of 70,000-90,000.
[0105] The particle size of the tantalum carbide is 800 nm, the purity is 99.99%, and it is purchased from Beijing Yanbang New Material Technology Co., Ltd.; the particle size of the metal sintering agent is 800 nm, the purity is 99.9%, and it is purchased from Jiangxi Guocai Technology Co., Ltd.
[0106] A method for preparing a high-crystallinity graphite protective layer comprises the following steps:
[0107] The carbide and the metal sintering agent are mixed and refined to obtain a mixed powder;
[0108] Adding a solvent and a dispersant to the mixed powder to obtain a mixed solution I;
[0109] Stirring the mixed solution I until there are no particles, and then ultrasonicating the mixed solution II;
[0110] Adhere the mixed solution II to the surface of the workpiece to be treated and dry;
[0111] After drying and sintering, a high-crystallinity graphite protective layer is obtained.
[0112] In the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is 3:1. The dispersant accounts for 3% of the total mass of the mixed solution I.
[0113] The amount of solvent added during the preparation of the mixed solution II is 5% of the mass of the solvent during the preparation of the mixed solution I.
[0114] The process of preparing the mixed powder includes: ball milling, the rotation speed of the ball milling is 600r / min, and the ball milling time is 16h.
[0115] The preparation process of the mixed solution II includes: using an ultrasonic machine for ultrasonication, the horn type of the ultrasonic machine is 25, the frequency of the ultrasonic machine is 20.5KHz, the power of the ultrasonic machine is 1800W, the ultrasonic output power is 80%, and the ultrasonic time of the ultrasonic machine is 20min.
[0116] The preparation process of the mixed solution II includes: replenishing the solvent during ultrasound, the interval time of the solvent replenishment is 1 minute, multiple ultrasounds are required, the interval time of the ultrasounds is 10 seconds, and the number of ultrasounds is 5 times.
[0117] The particle size of the mixed powder in the mixed solution II is 2 nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 20 μm.
[0118] The mixed solution II is attached by brushing.
[0119] The drying includes room temperature drying and vacuum drying oven drying, and the room temperature drying time is 1 hour.
[0120] The vacuum drying oven drying comprises: drying stepwise at 80° C., 120° C., and 150° C. for 4 h, 3 h, and 1 h, respectively.
[0121] The sintering includes sintering in an argon slightly positive pressure environment, heating to 800°C, 1500°C, 1800°C, and 2100°C at a heating rate of 5°C / min and keeping the temperatures for 20 minutes respectively, then heating to 2600°C at a heating rate of 1°C / min and keeping the temperatures for 1 hour, and then cooling naturally.
[0122] The workpiece to be processed is isostatic graphite with a particle size of 10 mm×10 mm×1 mm, purchased from Liaoning Xingwang Graphite Products Co., Ltd.
[0123] The electron microscope image of the prepared graphite protective layer is shown in Figure 1 The infrared spectrum of the prepared graphite protective layer is shown in Figure 2 The XRD pattern of the prepared graphite protective layer is shown in Figure 3 .
[0124] like Figure 1 As shown: The high-crystallinity graphite layer is tightly packed in structure, without cracks and holes, and the grain size is kept in the range of 2-5 microns. Compared with the untreated graphite substrate, the sintered graphite coating does not show D peak in the Raman spectrum, indicating that the defect density of the graphite coating is extremely low, and the surface is mainly composed of pure graphite without the presence of impurities such as TaC. This high-crystallinity, impurity-free graphite protective layer not only has large and dense grain size, but also has ideal structural integrity and surface uniformity.
[0125] From the XRD pattern ( Figure 3 ), we can observe the peaks of graphite and TaC, indicating that the structure of the protective layer is a multi-layer structure: the top layer is composed of polycrystalline graphite, and the lower layer of the coating is TaC. This double-layer structure design ensures the mechanical strength of the coating and provides excellent structural support.
[0126] Example 2
[0127] A high-crystallinity graphite protective layer, the preparation raw materials include carbide and metal sintering agent, the weight ratio of the carbide to the metal sintering agent is 5:3, and the preparation raw materials also include solvent and dispersant.
[0128] The carbide is tantalum carbide; the metal sintering agent is cobalt; the solvent is anhydrous ethanol; the dispersant is polyvinyl butyral, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with a weight average molecular weight of 70,000-90,000.
[0129] The particle size of the tantalum carbide is 1200 nm, the purity is 99.99%, and it is purchased from Beijing Yanbang New Material Technology Co., Ltd.; the particle size of the metal sintering agent is 1200 nm, the purity is 99.9%, and it is purchased from Jiangxi Guocai Technology Co., Ltd.
[0130] A method for preparing a high-crystallinity graphite protective layer comprises the following steps:
[0131] The carbide and the metal sintering agent are mixed and refined to obtain a mixed powder;
[0132] Adding a solvent and a dispersant to the mixed powder to obtain a mixed solution I;
[0133] Stirring the mixed solution I until there are no particles, and then ultrasonicating the mixed solution II;
[0134] Adhere the mixed solution II to the surface of the workpiece to be treated and dry;
[0135] After drying and sintering, a high-crystallinity graphite protective layer is obtained.
[0136] In the process of preparing the mixed solution I, the mass ratio of the solvent to the mixed powder is 3:1. The dispersant accounts for 3% of the total mass of the mixed solution I.
[0137] The amount of solvent added during the preparation of the mixed solution II is 5% of the mass of the solvent during the preparation of the mixed solution I.
[0138] The process of preparing the mixed powder includes: ball milling, the rotation speed of the ball milling is 500r / min, and the ball milling time is 20h.
[0139] The process of preparing the mixed solution II includes: using an ultrasonic machine for ultrasonication, the type of the ultrasonic machine's horn is 15, the frequency of the ultrasonic machine is 19.5KHz, the power of the ultrasonic machine is 1200W, and the ultrasonication time of the ultrasonic machine is 8 minutes.
[0140] The process of preparing the mixed solution II includes: replenishing the solvent during ultrasound, the interval time of the solvent replenishment is 1 minute, multiple ultrasounds are required, the interval time of the ultrasounds is 10 seconds, and the number of ultrasounds is 3 times.
[0141] The particle size of the mixed powder in the mixed solution II is 20 nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 20 μm.
[0142] The mixed solution II is attached by brushing.
[0143] The drying includes room temperature drying and vacuum drying oven drying, and the room temperature drying time is 1 hour.
[0144] The vacuum drying oven drying comprises: drying stepwise at 80° C., 120° C., and 150° C. for 4 h, 3 h, and 1 h, respectively.
[0145] The sintering includes sintering in an argon slightly positive pressure environment, heating to 800°C, 1500°C, 1800°C, and 2100°C at a heating rate of 5°C / min and keeping the temperatures for 20 minutes respectively, then heating to 2600°C at a heating rate of 1°C / min and keeping the temperatures for 1 hour, and then cooling naturally.
[0146] The workpiece to be processed is isostatic graphite with a particle size of 10 mm×10 mm×1 mm, purchased from Liaoning Xingwang Graphite Products Co., Ltd.
[0147] The electron microscope image of the prepared graphite protective layer is shown in Figure 4 .
[0148] like Figure 4 As shown in the figure: the high crystallinity graphite layer is more densely packed, and there is no grain boundary, that is, a whole large piece of graphite. Due to the increase of metal sintering agent content and powder particle size, a small part of the coating peels off. Figure 5 As shown: From the XRD spectrum, the peaks of graphite protective layer and tantalum carbide can be seen.
[0149] Example 3
[0150] A high-crystallinity graphite protective layer and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the carbide is molybdenum carbide; the metal sintering agent is iron;
[0151] The molybdenum carbide has a particle size of 800 nm and a purity of 99.95%, and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the iron has a particle size of 800 nm and a purity of 99.9%, and was purchased from Jiangxi Guocai Technology Co., Ltd.
[0152] The electron microscope image of the prepared graphite protective layer is shown in Figure 6 The XRD pattern of the prepared graphite protective layer is shown in Figure 7 .
[0153] like Figure 6 As shown: the morphology of the prepared coating is similar to that of Example 1, as Figure 7 As shown, the peaks of graphite and MoC (0.66) can be seen from the XRD spectrum.
[0154] Example 4
[0155] A high-crystallinity graphite protective layer and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the carbide is tungsten carbide; the metal sintering agent is nickel;
[0156] The tungsten carbide has a particle size of 800 nm and a purity of 99.95%, and was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; the nickel has a particle size of 800 nm and a purity of 99.9%, and was purchased from Jiangxi Guocai Technology Co., Ltd.
[0157] The electron microscope image of the prepared graphite protective layer is shown in Figure 8 The XRD pattern of the prepared graphite protective layer is shown in Fig. 9 .
[0158] like Figure 8 As shown: the morphology of the prepared coating is similar to that of Example 3, as shown in Fig. 9 As shown, the peaks of graphite and WC can be seen from the XRD pattern.
[0159] Example 5
[0160] A high-crystallinity graphite protective layer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the sintering includes sintering in an argon slightly positive pressure environment, heating to 800°C at a heating rate of 5°C / min and keeping warm for 20 minutes, 1500°C for 2 hours, 1800°C for 20 minutes, 2100°C for 20 minutes, then heating to 2600°C at a heating rate of 1°C / min and keeping warm for 1 hour, and cooling naturally.
[0161] The temperature of this embodiment is slightly higher than the melting point of Co. The longer holding time can improve the catalytic performance of the sintering agent. The C in the TaC component can precipitate more on the graphite surface, and the polycrystalline graphite formed in Example 1 is transformed into single-crystalline graphite. Although single-crystalline graphite exhibits superior physical properties in some aspects, due to its structural uniformity and lack of grain boundaries, this transformation also makes the single-crystalline layer easier to peel off. Therefore, compared with the polycrystalline layer formed in Example 1, the single-crystalline graphite layer of Example 5 lacks sufficient adhesion and toughness, and it is difficult to effectively provide the required protective effect. This lack of protective effect makes the graphite coating face greater risks in practical applications, especially under high temperature and mechanical load conditions, which can easily cause damage and failure of the coating.
[0162] The surface morphology is as follows Fig.11 , XRD pattern see Fig.10 . Fig.10 Contains only single crystal graphite.
[0163] Example 6
[0164] A high-crystallinity graphite protective layer and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the process of preparing the mixed powder does not include ball milling, and only manual stirring for 20 minutes is performed.
[0165] The spherical Co particles in the powder prepared in Example 6 are larger in size and spherical, and the distribution of Co and TaC particles is uneven. On the contrary, in the powder after ball milling in Example 1, the Co particles are evenly dispersed in the TaC particles, and it is difficult to observe the Co particles from the morphology. From the distribution of the EDS element, the two are evenly distributed. This distribution feature helps to improve the effect of the subsequent sintering process.
[0166] The surface of the sintered crystalline graphite protective layer in Example 6 has large pits and an uneven surface. This phenomenon may be related to the non-uniform distribution of particles, which leads to insufficient sintering in local areas, thus forming surface defects. This uneven surface not only affects the aesthetics of the coating, but may also have a negative impact on the thermal conductivity and electrical conductivity of the material.
[0167] In Example 6, we also prepared 9 samples containing crystalline graphite layers by adjusting the rotation speed and time of ball milling during the preparation of mixed powders. When the rotation speed was 600r / min and the ball milling time was 16h (parameters in Case 1), the sintering effect was best.
[0168] Fig.12 This is the eds element distribution diagram of the mixed powder after ball milling in Example 1.
[0169] Fig.13 This is an electron microscope image of the mixed powder in Example 6 without ball milling.
[0170] Fig.14 This is the surface morphology of the crystalline graphite layer prepared in Example 6 without sintering after ball milling.
[0171] Fig.15 Surface morphology of crystalline graphite layer prepared under different ball milling parameters.
[0172] Different ball milling parameters (see Table 1).
[0173] Table 1
[0174]
[0175]
[0176] Example 7
[0177] A high-crystallinity graphite protective layer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the ultrasonic parameters are different. The specific ultrasonic parameters are shown in Table 2 below.
[0178] Table 2
[0179]
[0180]
[0181] The mixed powder obtained after treatment in Examples 7-9 is the most uniform, with no obvious connection and clustering of Co particles, and the best effect after sintering. This uniform distribution significantly improves the overall effect of the coating during the sintering process, making the final graphite protective layer have the best performance. Fig.16 The electron microscope images of the mixed powder prepared under different ultrasonic parameters in Example 7 show that the uniformity can be judged by observing the distribution of spherical Co. Good particle distribution not only helps to fully integrate the components during the sintering process, but also ensures the consistency of the performance of the graphite protective layer. ; Fig.17The electron micrographs of the high-crystallinity graphite protective layer prepared under different ultrasonic parameters in Example 7 show the surface characteristics of the coating, including the morphology and structure of the particles, further verifying the importance of uniformly mixed powders obtained under different ultrasonic conditions in improving the quality of the coating.
[0182] Example 8
[0183] A high-crystallinity graphite protective layer and a preparation method thereof, the specific implementation method is the same as that of Example 1, except that anhydrous ethanol is replaced by deionized water. When deionized water is used as a solvent, the powder dissolution effect is poor. After the slurry is left to stand for a period of time, carbon powder that is not fully dissolved floats in the upper clear liquid, so it does not participate in subsequent coating and sintering.
[0184] Example 9
[0185] A high-crystallinity graphite protective layer and a preparation method thereof, the specific implementation method is the same as Example 1, except that anhydrous ethanol is replaced by toluene. A crystalline graphite layer can be successfully prepared, but its flatness and grain size are inferior and smaller than those prepared by anhydrous ethanol. This difference may be related to the solubility characteristics of toluene and its interaction with the powder. The results are shown in Fig.18 .
[0186] Example 10
[0187] A high-crystallinity graphite protective layer and a preparation method thereof, the specific implementation method is the same as that of Example 1, except that anhydrous ethanol is replaced by acetone. The surface of the crystalline graphite layer prepared by acetone is rough, and graphite grains of different sizes are mixed together. This non-uniformity of the grains causes the overall coating to have deficiencies in mechanical properties, which is manifested as easy powder shedding and relatively fragile. Fig.19 The microscopic image of the graphite protective layer prepared using acetone is shown, clearly reflecting the characteristics of surface roughness and uneven grain distribution.
[0188] Embodiment 11
[0189] A high-crystallinity graphite protective layer and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the dispersant accounts for 10% of the total mass of the mixed solution I.
[0190] After sintering, crystalline graphite will have holes and cracks, indicating that the overall density of the coating is insufficient. Fig. 20 The microstructural characteristics of the sintered graphite protective layer are shown, and the presence of pores and cracks can be clearly observed. These defects may have a negative impact on the mechanical properties and durability of the coating.
[0191] Performance Testing
[0192] The sample of the embodiment was prepared into a size of 10*10*2mm. The oxidation resistance was measured by oxidation at 800°C for ten minutes in a muffle furnace (air atmosphere), and the mass loss rate was calculated; the thermal conductivity was measured by a laser thermal conductivity meter NETZSCH LFA457, and the detection standard was based on the GB / T2 2588-2008 flash method to measure the thermal conductivity (thermal diffusion coefficient), and the detection temperature point was 800°C; the density was measured by a fixed density meter using the drainage method; the resistivity was measured by a four-probe tester, and according to the four-probe tester operating procedures TC / NIMTE-06-ZY-45-2021, the average value was taken after testing 5 points.
[0193] The test results are shown in Table 3.
[0194] Table 3
[0195]
Claims
1. A high crystallinity graphite protective layer, characterized in that: The preparation raw materials include carbide and metal sintering agent, the weight ratio of the carbide and the metal sintering agent is (2-7): (1-5), and the preparation raw materials also include solvent and dispersant; the thermal conductivity of the high crystallinity graphite protective layer is ≥55W / m·K, the oxidation mass loss is ≤33%, and the resistivity is ≤14×10 -4 Ω·cm. .
2. The high crystallinity graphite protective layer according to claim 1, characterized in that: The carbide includes at least one of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and tantalum zirconium carbide.
3. The high crystallinity graphite protective layer according to claim 1, characterized in that: The metal sintering agent includes at least one of iron, cobalt, nickel, niobium and zirconium.
4. The high crystallinity graphite protective layer according to claim 1, characterized in that: The particle size of the carbide is 500nm-1500nm, and the particle size of the metal sintering agent is 500nm-1500nm.
5. A method for preparing a high-crystallinity graphite protective layer according to any one of claims 1 to 4, characterized in that: The following steps are involved: The carbide and the metal sintering agent are mixed and refined to obtain a mixed powder; Adding a solvent and a dispersant to the mixed powder to obtain a mixed solution I; Stirring the mixed solution I until there are no particles, and then ultrasonicating the mixed solution II; Adhere the mixed solution II to the surface of the workpiece to be treated and dry; After drying and sintering, a high-crystallinity graphite protective layer is obtained.
6. The method for preparing a high-crystallinity graphite protective layer according to claim 5, characterized in that: The process of preparing the mixed powder comprises: ball milling, the rotation speed of the ball milling is 100r / min-700r / min, and the ball milling time is 10h-30h.
7. The method for preparing a high-crystallinity graphite protective layer according to claim 5, characterized in that: The preparation process of the mixed solution II includes: using an ultrasonic machine for ultrasonication, the type of the ultrasonic machine's horn is 10-20, the frequency of the ultrasonic machine is 15KHz-25KHz, the power of the ultrasonic machine is 1000W-2000W, and the ultrasonic time of the ultrasonic machine is 5min-15min.
8. The method for preparing a high-crystallinity graphite protective layer according to claim 5, characterized in that: The particle size of the mixed powder in the mixed solution II is 2nm-20nm, and the adhesion thickness of the mixed solution II on the surface of the workpiece to be processed is 10μm-30μm.
9. The method for preparing a high-crystallinity graphite protective layer according to claim 5, characterized in that: The drying includes room temperature drying and vacuum drying oven drying. The room temperature drying time is 0.5h-1.5h. The vacuum drying oven drying temperature is 70°C-160°C. The vacuum drying oven drying time is 1h-5h.
10. The method for preparing a high-crystallinity graphite protective layer according to claim 5, characterized in that: The sintering includes sintering in an inert gas slightly positive pressure environment, heating to 800°C-2100°C at a heating rate of 3°C / min-5°C / min, keeping warm for 10min-30min, then heating to 2500°C-2700°C at a heating rate of 1°C / min-3°C / min, keeping warm for 1h-3h, and cooling naturally.